Dual role of heme iron in cancer; promotor of carcinogenesis and an inducer of tumour suppression - Gamage, Sujani M.K.; Lee, Katherine T.W.; Dissabandara, D. Lakal O.; Lam, Alfred King-Yin; Gopalan, Vinod (Experimental and molecular pathology, 2021)
Heme is a crucial compound for cell survival but is also equipped with the potential to be toxic and carcinogenic to cells. However, with the recent advancement of knowledge regarding ferroptosis, the iron mediated cell death, heme can be postulated to induce tumour suppression through ferroptosis. This review summarizes the literature on the carcinogenic and anticarcinogenic properties of heme with specific emphasis on the alterations observed on heme synthesis, metabolism and transport in tumour cells. Literature search was performed in PubMed data base using the MeSH terms ‘heme iron or heme’, ‘cancer or carcinogenesis’ and ‘tumour suppression’ or ‘anticarcinogenic properties. Out of 189 results, 166 were relevant to the current review. Heme supports carcinogenesis via modulation of immune cell function, promoting inflammation and gut dysbiosis, impeding tumour suppressive potential of P53 gene, promoting cellular cytotoxicity and reactive oxygen species generation and modulating Nfr2 /HO-1 axis. The carcinogenic and anticarcinogenic properties of heme are both dose and oxygen concentration dependant. At low doses, heme is harmless and even helpful in maintaining the much-needed redox balance within the cell. However, when heme exceeds physiological concentrations, it could initiate and propagate carcinogenesis, due to its ability to produce reactive oxygen species (ROS). The same phenomenon of heme mediated ROS generation could be manipulated to initiate tumour suppression via ferroptosis, but the therapeutic doses are yet to be determined. Heme iron possesses powerful carcinogenic and anticarcinogenic properties which are dosage and oxygen availability dependant. •There are significant alterations in heme synthesis, transportation and metabolism in cancer cells•Heme generates reactive oxygen species supporting carcinogenesis•Heme impedes tumour suppressive potential of P53 gene•Heme modulates immune cell function, causes inflammation and gut dysbiosis, thereby initiating carcinogenesis•Heme has the potential to induce ferroptosis, and thereby tumour suppression